2019
DOI: 10.1016/j.pnpbp.2019.04.008
|View full text |Cite
|
Sign up to set email alerts
|

A review on shared clinical and molecular mechanisms between bipolar disorder and frontotemporal dementia

Abstract: Mental disorders are highly prevalent and important causes of medical burden worldwide. Cooccurrence of neurological and psychiatric symptoms are observed among mental disorders, representing a challenge for their differential diagnosis. Psychiatrists and neurologists have faced challenges in diagnosing old adults presenting behavioral changes. This is the case for early frontotemporal dementia (FTD) and bipolar disorder. In its initial stages, FTD is characterized by behavioral or language disturbances in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 247 publications
(374 reference statements)
2
30
0
1
Order By: Relevance
“…Different researches [ 33 , 34 , 35 ] point out that neurobehavioral disorders such as depression and anxiety have a repercussion on the deficit of neurocognitive functioning, finding an association between the low performance in executive functions and depressive symptomatology. Likewise, it has been found that anxiety has a repercussion on the decline of operative memory; both entities (depression and anxiety) also have a negative impact on the worsening of the quality of life and self-perception of health.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Different researches [ 33 , 34 , 35 ] point out that neurobehavioral disorders such as depression and anxiety have a repercussion on the deficit of neurocognitive functioning, finding an association between the low performance in executive functions and depressive symptomatology. Likewise, it has been found that anxiety has a repercussion on the decline of operative memory; both entities (depression and anxiety) also have a negative impact on the worsening of the quality of life and self-perception of health.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…This overlap in symptoms of bipolar disorder and bvFTD suggests possible shared origins and mechanisms between these two disorders and raises the question of whether bipolar disorder precedes or leads to bvFTD (17). Indeed, a number of investigators have reported a link between the two disorders (18,19), yet the exact association is unclear.…”
Section: Methodsmentioning
confidence: 99%
“…This is evidenced in individuals with frontotemporal dementia, particularly frontotemporal lobar degeneration, where atrophy in the frontal and temporal lobes of the brain leads to a profound decline in behavior and language ability (Rabinovici & Miller, ). Both frontotemporal dementia and frontotemporal lobar degeneration appear to have a shared pathological profile with certain psychiatric disorders, particularly bipolar disorder and major depressive disorder (Nascimento et al, ). This indicates that there may be a common underlying pathway driving cognitive disturbances in dementia and psychiatric disorders; the basal ganglia are highly likely to be involved as they have been shown to have abnormalities in both.…”
Section: The Basal Ganglia In Neurodegeneration and Dementiamentioning
confidence: 99%